Menjadi Orang Tua Kreatif bagi Anak Usia Dini di Masa New Normal: Becoming a Creative Parent for Early Childhood in the New Normal Period - Wahyuni, Fitri; Asfahani, Asfahani; Krisnawati, Nova (Absorbent Mind, 2021)
Learning activities organized by the school during the New Normal period were using social media assistance, such as whats app, zoom, google classroom, You Tube, Edmodo. This learning model is considered effective in breaking the chain of the spread of the corona virus. Learning and education patterns at an early age are filled with playing, running, and filled with joy in the learning process. Therefore, it takes a pattern of intense parenting and mentoring from parents to assist their children in taking online learning. Because in early childhood, it is the most important stage for their growth and development towards adult humans. This article was written using a literature study research method. The results showed that parenting patterns and mentoring can be done by parents in accompanying online learning. Among them can be done in the form of giving attention, supervision, and always coordinating with the school and other students' parents so that their children can learn independently and reflect Islamic values ​​according to the Al-Qur'an and Hadith.